Nierozerwalność małżeństwa w myśli Jana Chryzostoma - Zagórski, Dariusz (Vox Patrum, 2009)
The inseparability of marriage in the thoughts of St. John Chrysostom has its base on the fundament of that which is the unification of the spouses, very strong and undisputable, which is a result of the creation act of God and of His establishing. That unity finds its justification also in the mystical unification of Christ and the Church, which even more so points to the lastingness of the communion of the lives of two people joined together by the ties of marriage. The Antiochian, in accordance with the teachings of the Holy Scriptures is aware though of the dangers which are threatening that unity and seeking to undermine the inseparability of the union. They are the sins of lust and the disordered longings which lead to the evil of adultery, and therefore the sin of marital infidelity. This thesis on the inseparability of marriage is confirmed by Christ Himself, who in his teaching shows the agreement, of the initially seemingly to be in disagreement, teachings of the Old and New Law. The meaning of the Christological authority in this argument directed towards Christians was surely meant to strengthen in the faithful the responsibility for the communion of two persons and the care of all – not only spouses – for its inseparability. The words of the Savior also were to accent the actuality of this subject and its timeless meaning.